Studying Part-Time in Canada's Universities: A Social Change Perspective - Anisef, Paul (Canadian Journal of Higher Education, 1989)
Part-time university undergraduate students participation in the Canadian postsecondary education system has grown substantially over the past several decades. This growth raises questions concerning the factors influencing students' decisions to enrol full or part-time. The research presented here is based on the 1973-74 and 1983-84 National Postsecondary Student Surveys conducted by Statistics Canada and examines the changing influence of demographic, regional, socioeconomic and financial factors on registration status. The results indicate: (1) a diminishing impact of regional forces in choosing part-time registration status; (2) a dramatic increase of women in part-time studies (particularly older women); (3) that being married and having dependent children has become significantly less of a barrier for enroling part-time; (4) that students from more educationally advantaged backgrounds were more likely to register full-time in both survey years and the effect of parents' education remained unchanged across the surveys; (5) students that either applied for a government loan or borrowed to finance their studies were more likely to enrol full-time; this pattern was clearer for both sexes in 1983/84 than in 1974/75. These detailed findings are evaluated in terms of social changes in Canada, particularly with respect to women's increased participation in education and the labor market. While part-time university students constitute a relatively new clientele in higher education, their number and diversity is likely to grow, increasing our need to acquire new and more detailed information.